An optimal maintenance policy for a k-out-of-n system without monitoring component failures. Issue 2 (4th March 2019) - Park, Minjae; Lee, Jinpyo; Kim, Seungbeom
Abstract: In this study, an optimal maintenance policy is developed for a k -out-of- n: G system subject to two types of maintenance services, preventive maintenance and corrective maintenance. We investigate the optimal replacement age when a component failure is not detected immediately until a k -out-of- n: G system fails. The optimal maintenance policy is determined to minimize the expected total system cost when a generalized block replacement model is developed using downtime period. It is assumed that component failures are not monitored until a system failure, thus, a k -out-of- n: G system failure occurs. The downtime period of each failed component using order statistics for life time and age distributions for a k -out-of- n: G system is investigated. Numerical examples are discussed in order to demonstrate the applicability of the methodology derived from this paper.